Gentrification around the World, Volume II. Innovative Approaches. - (:unkn) unknown (Palgrave Macmillan, 2020)
Bringing together scholarly but readable essays on the process of gentrification, this two-volume collection addresses the broad question: In what ways does gentrification affect cities, neighborhoods, and the everyday experiences of ordinary people? In this second volume of Gentrification around the World, contributors contemplate different ways of thinking about gentrification and displacement in the abstract and “on-the-ground.” Chapters examine, among other topics, social class, development, im/migration, housing, race relations, political economy, power dynamics, inequality, displacement, social segregation, homogenization, urban policy, planning, and design. The qualitative methodologies used in each chapter—which emphasize ethnographic, participatory, and visual approaches that interrogate the representation of gentrification in the arts, film, and other mass media—are themselves a unique and pioneering way of studying gentrification and its consequences worldwide.
Keywords: Gentrifizierung; Verdrängung; Transformation; Bewohnerstruktur; Nachbarschaft; Segregation; Homogenisierung; Soziale Ungleichheit; Fallstudie; Stadtsoziologie; Internationaler Vergleich